2008
DOI: 10.1111/j.1365-2621.2008.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Common date palm in Tunisia: chemical composition of pulp and pits

Abstract: Date pulp and seeds (Phoenix dactylifera L.) of a mixture of some mature common varieties called 'Khalti', from the South-Eastern region of Tunisia, were evaluated for their main chemical composition. Studies were also conducted on the profiles of the extracted oil fatty acid. The following average values (on a dry-weight basis) were obtained from the pulp and pits, respectively: total sugars 63.38% and 8.12%, reducing sugars 51.56% and 6.63%, sucrose 11.82% and 1.49%, protein 3.86% and 5.31%, oil 0.26% and 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 18 publications
8
67
1
Order By: Relevance
“…The crude protein contents of dafe fruit were found between 1.43% (Sugei) and 2.55 % (Sukary), fiber contents of pulp were determined between 2.45% and 2.49%. Saafi et al, (2008) reported that date pulp contained 39.25% moisture, 63.38 % total sugars, 51.56% reducing sugars, 11.82% sucrose, 3.86% protein and 0.26 % fat.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The crude protein contents of dafe fruit were found between 1.43% (Sugei) and 2.55 % (Sukary), fiber contents of pulp were determined between 2.45% and 2.49%. Saafi et al, (2008) reported that date pulp contained 39.25% moisture, 63.38 % total sugars, 51.56% reducing sugars, 11.82% sucrose, 3.86% protein and 0.26 % fat.…”
Section: Resultsmentioning
confidence: 99%
“…The total phenolics content reported by Al-Farsi et al, (2005) for several date varieties ranged between 217 and 343 mg per 100 g. In our study, sucrose and reducing sugar contents of date pulp were determined to be 57.17% and 42.83% for Sukary, 0.59% and 99.41% for Khalas and 1.13% and 98.86% for sugei, respectively (Table 1). Date pits from the "Khalti" variety contained 6.88% of moisture, 8.12% of total sugar, 6.63% reducing sugar, 1.49% of sucrose, 5.31% of protein and 8.33% of fat (Saafi et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Author ( Economically, the date palm fruit and by-product are precious for their nutritional and dietetic properties and income generating for oasis' populations (Al-shahib and Marshall, 2003;Chao and Krueger, 2007;Saafi et al, 2008). "Bayoud" disease ( Figure 1) is the most destructive fungal disease of date palm.…”
Section: Introductionmentioning
confidence: 99%